Compressive Strength and Water Permeability Performance of Micronised Biomass Silica Concrete - Adnan, S.H.; Abdul Rahman, I.; Lee, Y.L.; Yusof, H. (International Journal of Integrated Engineering, 2009)
Concrete is a common material that is widely used in construction industry. Cement is the main material component for producing concrete but its production has lead into CO2 emission. This work presents a study on Micronised Biomass Silica (MBS) that can be used as pozzolan material which can enhance the quality of concrete. The material can be produced from a by-product of biomass agricultural waste but for this study rice husk has been used. From the chemical analysis, MBS has a chemical composition that is fulfill the standard requirement for becoming pozzolan material. The result of MBS concrete shows that the MBS material can enhance the performance of concrete by increasing the compressive strength development and reducing the water permeability. The drawback of MBS is the workability of fresh concrete but can be rectify by using superplasticizer. By replacing up to 12% of cement, MBS material gives the highest performance in term of strength and permeability of the concrete.